Dynamic analysis of an offshore wind turbine under random wind and wave excitation with soil-structure interaction and blade tower coupling. Issue 125 (October 2019) - Banerjee, Arundhuti; Chakraborty, Tanusree; Matsagar, Vasant; Achmus, Martin
Abstract: This study investigates the dynamic response of a 5 MW offshore wind turbine with monopile foundation subjected to wind and wave actions. The work includes dynamic interaction between the monopile and the underlying soil subjected to realistic offshore random wind and wave loading modeled using Von karman spectrum and Pierson Moskowitz spectrum respectively. The study also incorporates the effect of blade tower coupling in the analysis. The offshore wind turbine tower is modeled herein as a multi-degree of freedom system (MDOF) and it comprises of a rotor blade system, a nacelle, and a flexible tower. The mass of the rotor, blade, and nacelle are lumped at the top of the tower for simplicity. Separately, the effect of the rotation of blades has also been incorporated in the work. The rotational effect of the blades is taken into account considering shape filters using von Karman spectrum. The soil-structure interaction effect at the foundation level is modeled using equivalent spring-dashpot model for embedded foundations. The results are studied in time as well as frequency domain for both wind and wave loading. It has been observed that soil structure interaction effect greatly alters the response of the offshore wind turbine structure not only in the parked condition but also in operational conditions when blade tower coupling is also included. The effect of blade tower coupling and SSI on the response of the structure are observed more coherently in the case of wave induced loading. Highlights: Dynamic interaction studied between the monopile and the underlying soil subjected to realistic random wind and wave loading. Effect of blade tower coupling incorporated in the analysis. Rotational effect of the blades taken into account considering shape filters using von Karman spectrum. Effect of blade tower coupling and soil structure interaction on the displacement, acceleration, base shear and base moment response of the structure studied in detail. The results of the study are studied in time as well as frequency domain for both wind and wave loading.